Consumer Behavior Analysis in Pangkalpinang: Perception as Intervening of Hydroponic Purchase Decision with STP Approach - Gianina, Dewa Ayu; Yamin, Muhammad; Oktarina, Selly (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The rapid rise in urban growth and health-conscious behavior in Pangkalpinang has spurred a demand for hydroponic vegetables. This study seeks to explore the factors shaping consumers' decision to purchase hydroponic vegetables in this area. By employing a quantitative research design, survey data were gathered from 170 respondents, focusing on demographic characteristics, variables related to socioeconomic status, perception as psychological influence, and marketing elements. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to identify the key predictors of purchasing behavior, alongside the application of the STP (Segmentation, Targeting, Positioning) strategy to enhance sales. The results show that most consumers are women working in the private sector, with a bachelor's degree, earning between Rp 4,000,000 and Rp 6,000,000, aged 17-25 years, married, and residing in Gabek District. The factors directly and significantly influence the decision to purchase hydroponic vegetables are product, income and perception. Price, however, does not have a direct effect. Nonetheless, price has a significant indirect impact on purchasing decision through its influence on perception. The marketing strategy employs the STP model to create an appealing product image and attract potential consumers. This approach integrates excellent customer service, attractive packaging, promotional pricing, and product innovation.